In Situ Raman Monitoring of the Formation and Growth of Carbon Nanotubes via Chemical Vapor Deposition. (2015) - Reinhold-López, Karla; Braeuer, Andreas; Romann, Bettina; Popovska-Leipertz, Nadejda; Leipertz, Alfred
Abstract: An in situ measurement technique based on Raman spectroscopy is established to simultaneously monitor the parameters of interest of the solid and gas phases during the formation and growth of carbon nanotubes (CNT) in a cold wall reactor for catalytic chemical vapor deposition (CCVD). Iron nanoparticles were used as a catalyst and acetylene as a carbon source. This new developed technique makes possible the simultaneous in situ measurement of the gas phase composition, the gas phase temperature and the micro structure of the deposited CNTs, such that finally the decomposition of the carbon source and its effect on the gas temperature and on the CNTs formation and growth can be followed as a function of the reaction time. Comprehensive qualitative and quantitative analyses have been performed to assess the catalyst performance with respect to the growing carbon nanostructures. On the basis of the real-time in situ Raman spectra of the emerging solid phase, the moment of nucleation or first signal detection, the time-range of the CNT growth and the end of the deposition is monitored via the characteristic D and G Raman bands for carbon materials. Information about catalytic activity is qualitatively provided and the estimated in situ D/G ratio reveals the defect and disorder content of the growing nanostructures. The Raman spectroscopy setup for the gas phase analysis exhibits high detection sensitivity as well as high accuracy and precision. Correlation could be found between the catalyst activity, acetylene conversion and micro structure of the resulting CNTs.